Comparative proteomics reveals key proteins recruited at the nucleoid of Deinococcus after irradiation‐induced DNA damage. Issue 23 (4th December 2013) - de la Tour, Claire Bouthier; Passot, Fanny Marie; Toueille, Magali; Mirabella, Boris; Guérin, Philippe; Blanchard, Laurence; Servant, Pascale; de Groot, Arjan; Sommer, Suzanne; Armengaud, Jean
Abstract : The nucleoids of radiation‐resistant Deinococcus species show a high degree of compaction maintained after ionizing irradiation. We identified proteins recruited after irradiation in nucleoids of Deinococcus radiodurans and Deinococcus deserti by means of comparative proteomics. Proteins in nucleoid‐enriched fractions from unirradiated and irradiated Deinococcus were identified and semiquantified by shotgun proteomics. The ssDNA‐binding protein SSB, DNA gyrase subunits GyrA and GyrB, DNA topoisomerase I, RecA recombinase, UvrA excinuclease, RecQ helicase, DdrA, DdrB, and DdrD proteins were found in significantly higher amounts in irradiated nucleoids of both Deinococcus species. We observed, by immunofluorescence microscopy, the subcellular localization of these proteins in D. radiodurans, showing for the first time the recruitment of the DdrD protein into the D. radiodurans nucleoid. We specifically followed the kinetics of recruitment of RecA, DdrA, and DdrD to the nucleoid after irradiation. Remarkably, RecA proteins formed irregular filament‐like structures 1 h after irradiation, before being redistributed throughout the cells by 3 h post‐irradiation. Comparable dynamics of DdrD localization were observed, suggesting a possible functional interaction between RecA and DdrD. Several proteins involved in nucleotide synthesis were also seen in higher quantities in the nucleoids of irradiated cells, indicative of the existence of a mechanism for orchestrating the presence of proteins involved in DNA metabolism in nucleoids in response to massive DNA damage. All MS data have been deposited in the ProteomeXchange with identifier PXD00196 (http://proteomecentral.proteomexchange.org/dataset/PXD000196 ).